2016
DOI: 10.2119/molmed.2015.00207
|View full text |Cite
|
Sign up to set email alerts
|

Blood-brain Barrier Remodeling during Brain Metastasis Formation

Abstract: Our understanding of the process of metastatic progression has improved markedly over the past decades, yet metastasis remains the most enigmatic component of cancer pathogenesis. This lack of knowledge has serious health-related implications, since metastasis is responsible for 90% of all cancer-related mortalities. The brain is considered a sanctuary site for metastatic tumor growth, where the blood-brain barrier (BBB) and other components of the brain microenvironment, provide protection to the tumor cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 78 publications
(162 reference statements)
0
50
0
5
Order By: Relevance
“…Preclinical studies demonstrated the stem cell-specific signalling by the Wnt and Notch pathways to be associated with the development of BM [38,39]. Angiogenic factors-the vascular endothelial growth factor (VEGF), angiopoietin-2 and chemokine receptor type 4 (CXCR-4)-have been identified as the specific drivers of BM developmental process [40][41][42][43][44][45]. Dysregulation of these factors helps cancer cells to disrupt the blood-brain barrier followed by their extravasation and migration into the brain parenchyma.…”
Section: Molecular and Genetic Biomarkers Other Than Hormone And Her2mentioning
confidence: 99%
“…Preclinical studies demonstrated the stem cell-specific signalling by the Wnt and Notch pathways to be associated with the development of BM [38,39]. Angiogenic factors-the vascular endothelial growth factor (VEGF), angiopoietin-2 and chemokine receptor type 4 (CXCR-4)-have been identified as the specific drivers of BM developmental process [40][41][42][43][44][45]. Dysregulation of these factors helps cancer cells to disrupt the blood-brain barrier followed by their extravasation and migration into the brain parenchyma.…”
Section: Molecular and Genetic Biomarkers Other Than Hormone And Her2mentioning
confidence: 99%
“…Brain is considered to be a sanctuary site because of the blood–brain barrier (BBB). The BBB is a physiological obstruction to the delivery of systemic therapies to the brain parenchyma and central nervous system (CNS) [15] and it plays a key role in tumor cell migration and colonization to the brain [16]. For these reasons, there are large differences in biomarkers expressed between the primary tumor and metastases, especially for BM [17].…”
Section: Introductionmentioning
confidence: 99%
“…Endothelial cells of brain vessels serve as a mechanical barrier, and astrocytes and microglia are capable of destroying tumor cells. However, after brain colonization, the cerebral endothelial cells, astrocytes, and microglia provide crucial support in the growth and proliferation of tumor cells, and BBB protects cancer cells from influencing the immune system and most anticancer drugs [9].…”
Section: Role Of the Blood-brain Barrier In The Formation Of Brain Mementioning
confidence: 99%
“…The availability of MELTF on the melanoma cell membrane determines their ability to penetrate through the BBB. High levels of STAT3 in melanoma BM compared to primary tumor cells indicate a relationship between STAT3 expression and tumor cell migration to the brain [9]. Thus, the identification of tumor cells specific markers of penetration through the BBB can be a basis for the development of specific methods for the prevention of BM.…”
Section: Role Of the Blood-brain Barrier In The Formation Of Brain Mementioning
confidence: 99%